Formulation, Optimised and Evaluation of Mouth dissolving film of Amoxapine - Yadav, Anjudip; Tripathi, Shailendra; Sharma, Vandana; Soni, S. L.; Tiwari, Deeksha (Asian Journal of Pharmaceutical Research and Development, 2021)
Amoxapine is orally active, acts by decreasing the reuptake of norepinephrine and serotonin and used for depression. The research work was undertaken to formulate, optimize and evaluation of mouth dissolving film of amoxapine, so that rapid release of drug constituents and give faster action. Mouth dissolving film (MDF) is a better alternative compared to oral disintegrating tablet due to patient compliance. Amoxapinebelongs to Biopharmaceutics Classification System ClassII, means drug have low solubility. The problem is resolved by using Polomer188. MDF prepared by solvent casting method. For preparation of film, hydrophilic polymers were selected as film forming polymers. Different polymers were selected such as different grades of Hydroxyl Propyl Methyl Cellulosei.e. E5, E15, E50.Selection of plasticizer was also done and PEG-400 was found best giving better results. It was found that formulation contain desiredphysio-mechanical properties. Keywords- Depression, Patient Compliance, BCS II, Polomer188, Solvent Casting